The Use of Swearing Words Differences Between Men and Women Communication in University - Mutiara Sintya Dewi; Nabila Khoirunnisa; Nadia Deba Claradista; Teguh Sarosa (PRASASTI: Journal of Linguistics, 2025)
This research investigates gender-based differences in the use of swear words among university students, exploring whether significant variations exist in their daily communication. Adopting a descriptive qualitative approach, data were collected through questionnaires distributed to 48 participants, focusing on their perceptions, attitudes, and experiences with swearing. The findings reveal notable distinctions between male and female swearing behavior. Men were observed to use swear words more frequently and openly, often as a means of expressing camaraderie, asserting dominance, or emphasizing their emotions in social interactions. In contrast, women tended to use swear words more selectively and situationally, primarily in private settings or emotionally charged moments, reflecting societal expectations of politeness and decorum. These differences highlight the impact of gender norms, personality traits, and social contexts on linguistic choices, with women facing greater stigma for using profanity than men. Additionally, the study underscores the evolving role of swearing as a multifaceted linguistic tool for expressing emotions, asserting identity, and navigating social relationships. By shedding light on these dynamics, the research contributes to a deeper understanding of gendered communication and emphasizes the importance of addressing stereotypes to foster more inclusive and effective interactions within academic and social environments.